An Investigation Into The Pattern and Motives of R&D Internationalisation of Big UK Pharmaceutical Companies - Gwee, Chin Hoo (2017)
Pharmaceutical sector as a global-born and knowledge-based economy, is well noted with its extensive internationalisation of R&D activities. However, the pattern and the motives of these decisions are scarcely studied and understood. As such, this study is driven by the objective of exploring the pattern and motives of R&D internationalisation of selected large global pharmaceutical firms. Drawing conclusion from case studies based on three large, UK-based pharmaceutical corporations, the study has suggested four major motives for internationalising R&D activities: strategic assets (knowledge) seeking, market seeking, efficiency seeking and as a mean to conduct CSR. Meanwhile, the pattern of their global R&D activities are also revealed in term of the location choices and strategy in conducting it. Lastly, the study proposes that the patterns of R&D internationalisation is greatly affected by the firm motives underlying the decisions.